Sonochemical preparation of PbWO4 crystals with different morphologies - Titipun Thongtem (2018)
PbWO4was prepared from Na2WO4·2H2O and Pb(OAc)2·3H2O in a solution containing a cationic surfactant (N-cetyl pyridinium chloride) using the sonochemical process (ultrasonic irradiation). The product morphologies, characterized using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), were controlled by the surfactant, pH values and ultrasonic irradiation times. X-ray diffraction (XRD) and selected area electron diffraction (SAED) studies revealed diffraction patterns in good agreement with the simulation model, along with Fourier transform infrared (FTIR) and Raman analyses showed a W-O stretching band consistent with tetragonal PbWO4. Photoluminescent properties of the pine tree shaped products were also investigated. © 2008 Elsevier Ltd and Techna Group S.r.l.